Pentingnya Vitamin A Pada Mata - Muhammad Afda Nuzula; Salsabila Audrina Putri; Shelina Dwi Ambarwati; Febi Yuspa Nastiti; Liss Dyah Dewi Arini (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The recent increase in eye health issues among children is suspected to be due to a lack of vitamin A or exposure to radiation from electronic devices. Controlling children's use of electronic technology poses a challenge for both society and parents. Active involvement of the government and the community is needed to address this issue. Vitamin A supplements have become a common strategy in preventing and addressing vitamin A deficiency in public health programs. The prevalence of blindness in Indonesia is of serious concern, with the highest rate in Southeast Asia. Vitamin A is essential in maintaining eye and overall body health. Efforts to provide vitamin A supplements are an effective strategy in preventing and addressing vitamin A deficiency. Additionally, vitamin A plays a role in maintaining reproductive organ health, protecting the body from the risk of cancer and chronic diseases, and strengthening the immune system. Vitamin A deficiency can lead to visual impairment, anemia, and decreased immunity to infections. Attention to vitamin A intake in daily diet is crucial, but maintaining a balance is necessary to avoid toxicity. Awareness and education about the importance of vitamin A need to be enhanced, and the government and society must work together to prevent and address issues related to vitamin A deficiency..